2018
DOI: 10.1111/mec.14940
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal divergence and selection against immigrant seeds in forest and dune populations of the partially mycoheterotrophicPyrola rotundifolia

Abstract: Plant populations occupying different habitats may diverge from each other over time and gradually accumulate genetic and morphological differences, ultimately resulting in ecotype or even species formation. In plant species that critically rely on mycorrhizal fungi, differences in mycorrhizal communities can contribute to ecological isolation by reducing or even inhibiting germination of immigrant seeds. In this study, we investigated whether the mycorrhizal communities available in the soil and associating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The few available studies have shown that, in some cases, mycorrhizal communities shift during ontogenetic development. For example, germinating seeds and the first underground stages of several Pyrola (Ericaceae) species have been shown to associate with multiple partners simultaneously, but the fungi that associated with seeds differed from those associating with adult plants (Hashimoto et al, ; Hynson, Weiss, Preiss, Gebauer, & Treseder, ; Jacquemyn, Waud, & Brys, ; Johansson, Bahram, Tedersoo, Kõljalg, & Eriksson, ), suggesting that plants may serially associate with different partners rather than specializing on a single ‘best’ partner. Similarly, the mycorrhizal communities associating with protocorms and adult plants of the orchid Liparis loeselii (Orchidaceae) were diverse and varied among life cycle stages (Waud, Brys, Landuyt, Lievens, & Jacquemyn, ).…”
Section: Introductionmentioning
confidence: 99%
“…The few available studies have shown that, in some cases, mycorrhizal communities shift during ontogenetic development. For example, germinating seeds and the first underground stages of several Pyrola (Ericaceae) species have been shown to associate with multiple partners simultaneously, but the fungi that associated with seeds differed from those associating with adult plants (Hashimoto et al, ; Hynson, Weiss, Preiss, Gebauer, & Treseder, ; Jacquemyn, Waud, & Brys, ; Johansson, Bahram, Tedersoo, Kõljalg, & Eriksson, ), suggesting that plants may serially associate with different partners rather than specializing on a single ‘best’ partner. Similarly, the mycorrhizal communities associating with protocorms and adult plants of the orchid Liparis loeselii (Orchidaceae) were diverse and varied among life cycle stages (Waud, Brys, Landuyt, Lievens, & Jacquemyn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Their idea was that the soil fungi differed between the two habitat types (populations), which they found it did, and that the fungi at one site would be more conducive to germination of its native seeds than to immigrant (nonnative) seeds from the other site. Overall, Jacquemyn et al (2018) found that natives germinated somewhat better than nonnatives. After 2 years of burial, there were, on average, more seedlings from native than from nonnative seeds in packets from five of the six subpopulations.…”
Section: Resultsmentioning
confidence: 98%
“…Jacquemyn et al (2018) compared the germination of seeds of P. rotundifolia during burial in a reciprocal seed transplant study between populations in an inland temperate deciduous forest and coastal sand dunes/dune slacks in Belgium. Native and nonnative seeds to the two populations were buried reciprocally for 2 years in three forest and three dune subpopulations (replicates).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mycorrhizal community changes during ontogenetic development have been shown in other species. For example, the fungi that associate with seeds of several Pyrola (Ericaceae family) species differ from those coupled with adult plants ( Hashimoto et al 2012 ; Hynson et al 2013 ; Johansson et al 2017 ; Jacquemyn et al 2018 ). This indicates that some plants may serially associate with different fungal partners rather than choosing a single best partner.…”
Section: Introductionmentioning
confidence: 99%